Perioperative management of a redo aortic root replacement in a patient with severe factor XI deficiency. Issue 2 (4th February 2018) - Fitzsimons, Michael G.; Leaf, Rebecca Karp; Mack, Johnathan; Bendapudi, Pavan K.; Shen, Tao; Cameron, Duke E.
Abstract: Factor XI deficiency is associated with significant bleeding in the setting of trauma and surgery. We present a patient with FXI deficiency and multiple red blood cell allo‐antibodies requiring repeat aortic root replacement and discuss the perioperative management of patients with FXI deficiency undergoing cardiac surgery.